Strategy in Airline Loyalty Frequent Flyer Programs - de Boer, Evert R. (Springer International Publishing, 2018)
This book offers the first comprehensive exploration of frequent flyer programs. By combining academic research with extensive insights and examples from the actual business world, it explores the key drivers and strategies of airline loyalty marketing today in an unprecedented manner. Strategy in Airline Loyalty also explores how the programs have evolved over time from marketing programs to financial powerhouses, identifying both the catalysts for change, as well as the strategic options and underlying trade-offs available to airlines. Covering diverse angles ranging from behavioral economics, to accounting, and structural design, the book reviews every core aspect of frequent flyer programs and offers extensive frameworks and definitions. The book provides a useful and complete reference for researchers, and helps those interested in frequent flyer programs to develop a better understanding of their past, present and future.